Imaginative transcripts : selected literary essays - Spiegelman, Willard (Oxford University Press, 2009)
Willard Spiegelman is considered one of the finest critics of poetry writing in modern day. This volume collects his best work on the subject, offering essays that span his entire career and chart his changing relationship to an elusive form.